Case report: dermoscopic and histological aspects of skin graft and perigraft hyperpigmentation in acral location - Bruna Tuma; Sergio Yamada; Rodrigo Almeida de Medeiros; Mauricio Mendonca do Nascimento; Sergio Henrique Hirata (Sociedade Brasileira de Dermatologia, 2014)
Little is known about the use of dermoscopy in skin grafting. We describe the case of a patient with skin grafting and surrounding pigmentation on acral region. The dermoscopic findings were similar to those of benign acral lesions (lattice-like pattern) and reactive pigmentations (fine striae). Histopathology revealed pigment leakage and increased number of melanocytes. It is believed that this phenomenon occured as the result of an inflammatory stimulus.